EVALUASI KEBIJAKAN PEMBANGUNAN SUMUR RESAPAN DI INDONESIA: TINJAUAN REGULASI, PERMASALAHAN DAN POTENSI DAMPAK - Andi Setyo Pambudi (Jurnal Kebijakan Pembangunan Daerah, 2025)
Climate change, rapid urbanization, and land-use conversion have disrupted Indonesia’s hydrological balance, leading to frequent floods during the rainy season and water scarcity during dry periods. Infiltration wells have emerged as a technical solution for water conservation, yet their implementation remains suboptimal. Previous studies have primarily focused on technical aspects, while integrated evaluations covering regulatory, institutional, and socio-economic dimensions are still lacking. This research addresses that gap by comprehensively evaluating infiltration well policies to support national water resilience targets. The study aims to analyze regulatory frameworks, identify technical and institutional challenges, and formulate sustainable development strategies. Using a qualitative approach, the research combines literature review of laws, standards, and academic journals with a Focus Group Discussion (FGD) involving 15 participants from water agencies in five provinces. Three key findings emerged: (1) infiltration wells are not yet integrated into regional planning documents such as RPJMD and spatial plans; (2) technical quality and maintenance systems are weak and inconsistent; and (3) cross-sectoral coordination and community involvement are minimal. Policy recommendations include harmonizing national-local regulations, mandating basic hydrogeological assessments, establishing inter-agency task forces, and offering incentives for developers and communities. The study highlights the urgency of collaborative, region-specific approaches to scale up infiltration well development in Indonesia.